2014
DOI: 10.1016/j.surg.2014.03.013
|View full text |Cite
|
Sign up to set email alerts
|

The role of enteral fat as a modulator of body composition after small bowel resection

Abstract: Background Following massive small bowel resection (SBR), a postoperative diet that is high in fat is associated with enhanced villus growth. The purpose of this study was to further elucidate the quantity and composition of enteral fat in structural and metabolic changes after SBR. Methods C57/Bl6 mice underwent a 50% proximal SBR. Mice were then randomized to receive a low fat diet (LFD- 12% kcal fat), medium fat diet (MFD-44% kcal fat), or high fat diet (HFD-71% kcal fat) ad lib. In a separate experiment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…All subjects were maintained on the same diet that they had been assigned to preoperatively, i.e., obese rats were kept on the high-fat diet, and non-obese rats were kept on regular chow. Previous work on intestinal adaptation after resection demonstrated that a high-fat postoperative diet enhanced villus length and smooth muscle contraction with respect to a low-fat diet 4 19 20 . So there may have been the possibility that the different postoperative diets influenced intestinal adaptation independent of preoperative body composition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All subjects were maintained on the same diet that they had been assigned to preoperatively, i.e., obese rats were kept on the high-fat diet, and non-obese rats were kept on regular chow. Previous work on intestinal adaptation after resection demonstrated that a high-fat postoperative diet enhanced villus length and smooth muscle contraction with respect to a low-fat diet 4 19 20 . So there may have been the possibility that the different postoperative diets influenced intestinal adaptation independent of preoperative body composition.…”
Section: Discussionmentioning
confidence: 99%
“…Murine studies of extensive intestinal resection have suggested that the amount of fat in a postoperative diet and/or a post-resectional hyperphagic mechanism might account for the retention of body weight, with the increased caloric intake compensating for the loss of digestive and absorptive area of the intestine 4 . Our intention with the present study was to determine whether rats with pre-existing obesity (induced with a high-fat diet) would have improved outcomes after massive intestinal resection compared to non-obese rats.…”
mentioning
confidence: 99%
“…High-fat diets have been shown to enhance stemness by increasing the number and function of LGR5+ cells through activation of peroxisome proliferator-activated receptor-δ signaling 67 . High-fat diets, and omega-3 fatty acids in particular, also have been shown to enhance adaptation after massive small-bowel resection in rodent models 68, 69, 70. In infants with SBS, fish oil–based intravenous lipid emulsions help ameliorate or reverse cholestasis associated with parenteral nutrition 70, 71.…”
Section: Discussionmentioning
confidence: 99%
“… 67 High-fat diets, and omega-3 fatty acids in particular, also have been shown to enhance adaptation after massive small-bowel resection in rodent models. 68 , 69 , 70 In infants with SBS, fish oil–based intravenous lipid emulsions help ameliorate or reverse cholestasis associated with parenteral nutrition. 70 , 71 However, no studies have addressed the effect of high-fat enteral diets on adaptation, enteral independence, or weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…Kollman, et al demonstrated that resected rats fed LCPUFA-enhanced diets demonstrated significantly increased intestinal mucosal mass in a dose-dependent manner [65]. Another study found that in a mouse model, menhaden oil (versus saturated and monounsaturated fats) resulted in the highest percent of lean mass and greatest weight retention after SBR, though adaptation was indistinguishable across diets [66]. The benefit of LCFAs is attributed to its anti-inflammatory metabolite (prostaglandins), as inhibition with aspirin, a cyclo-oxygenase inhibitor, reduces the predicted intestinal adaptive response [67].…”
Section: Fatmentioning
confidence: 99%